FAKTOR-FAKTOR YANG MEMENGARUHI PURCHASE INTENTION DAN PURCHASE DECISION PADA PRODUK HIJAB PREMIUM BUTTONSCARVES - Juliana, Sartika; Suhud, Usep; Rahmi, Rahmi (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
This study was conducted with the aim of examining the influence of viral marketing, electronic word of mouth, and brand awareness on purchase intention. and the influence of viral marketing, electronic word of mouth, brand awareness, and purchase intention on purchase decisions. This study using survey or questionnaires by office forms for method to collect data with a sample of 205 respondents. This research uses a quantitative with SEM (Structural Equation Modelling) for data analysis techniques. The results of this study show that viral marketing, electronic word of mouth, and brand awareness each have a positive and significant influence on purchase intention. Brand awareness and purchase intention each also have an influence on purchase decisions. While viral marketing and electronic word of mouth were each found not to have a significant enough influence on purchase decisions.